Effects of vitamin D supplementation on serum 25-hydroxyvitamin D concentrations and physical performance in athletes: A systematic review and meta-analysis of randomized controlled trials - Farrokhyar, F.; Sivakumar, G.; Savage, K.; Koziarz, A.; Jamshidi, S.; Ayeni, O. R.; Peterson, D.; Bhandari, M. (Sports Medicine, 2017)
Background: There is currently no systematic review examining the effects of vitamin D supplementation among athletes. A rigorous systematic review and meta-analysis is important to provide a balanced view of current knowledge on the effect of vitamin D on serum 25-hydroxyvitamin D [25(OH)D] concentrations and physical performance. Objectives: This systematic review of randomized controlled trials (RCTs) evaluated the effects of oral vitamin D supplementation on serum 25(OH)D concentrations and physical performance in athletes. Methods: Multiple electronic databases were searched, and study eligibility, methodological quality assessment, and data extraction were completed independently and in duplicate. Studies were stratified by baseline vitamin D sufficiency, season, and latitude. A cut-off of 30 ng/ml (75 nmol/l) of 25(OH)D was used for sufficiency. Absolute mean differences (AMDs) between vitamin D and placebo using random effects analysis, and heterogeneity using Q statistic and I2 index, were calculated. AMD with 95% confidence interval (CI), p value, and I2 are reported. Results: In total, 13 RCTs (2005-2016) with 532 athletes (vitamin D 311, placebo 221) were eligible. A total of 433 athletes (vitamin D 244, placebo 189) had complete outcome data. Among athletes with baseline values suggesting insufficiency, vitamin D supplementation led to significant increases from 3000 IU (AMD 15.2 ng/ml; 95% CI 10.7-19.7, p < 0.0001, I2 = 0%) and 5000 IU (AMD 27.8 ng/ml; 95% CI 16.9-38.8, p < 0.0001, I2 = 78%) per day at >45° latitudes. Both doses led to sufficiency concentrations during winter months. Among athletes with baseline vitamin D suggesting sufficiency, serum 25(OH)D sufficiency was maintained from different doses at both latitudes. Of 13 included trials, only seven measured different physical performances and none demonstrated a significant effect of vitamin D supplementation during 12 weeks of follow-up. Conclusion: Despite achieving sufficiency in vitamin D concentrations from =3000 IU supplementation, physical performance did not significantly improve. Between-study heterogeneity was large, and well-designed RCTs examining the effect of vitamin D supplementation on serum 25(OH)D concentrations, physical performance, and injuries in different sports, latitudes, ethnicities, and vitamin D status are needed.